The Employment Sector of a Regional Policy Simulation Model - Treyz, George I.; Friedlaender, Ann F.; Stevens, Benjamin H. (The Review of Economics and Statistics, 1980)
D ESPITE the rapid development of techniques of regional economic analysis during the past fifteen years, most regional models have continued to focus upon selected aspects of the regional economy rather than upon its totality. Economic base models and regional input-output models have concentrated upon the relationships between the output and employment in the export sectors and the local sectors;' comparative cost models have concentrated upon the response of the export sectors to changes in relative regional production costs;2 and regional econometric models have concentrated upon the determinants of employment in the export sectors and the relationships between regional economic activity and that of the nation.3 This disparate collection of partial-equilibrium models generally does not make it possible to determine the full general-equilibrium effects of a given economic change on the total regional economy. For example, although economic base/input-output models permit the estimation of the indirect and induced employment and output effects arising from a change in final demand or the level of activity in the export sector, they treat the level of activity in the export sector as exogenous and do not permit factor substitution. Similarly, although comparative cost models explicitly recognize that the location of export industries is largely determined by relative production costs, they do not consider the interrelationships among the industries within the export and local sectors or the role that factor substitution can play in regional employment levels. Finally, although regional econometric models generally use a neoclassical labor demand function, and hence explicitly consider factor substitution, they do not fully differentiate between the factor-substitution and production cost effects of a change in regional input prices. Furthermore, they do not account for the full set of linkages among the industries in the export and local sectors. The growing need for comprehensive regional models for planning and policy analysis suggests that there would be substantial value in having models that synthesize the relevant aspects of existing regional economic theory into a single integrated construct. Such an integrated model would be useful for both forecasting and policy evaluation and should include the following fea-. tures: First, it should recognize that factor substitution is possible and that an increase in the regional price of any given factor will tend to cause substitution in favor of other factors (the factorsubstitution effect); Second, it should recognize that an increase in any input price in a region relative to that in other regions will tend to increase production costs in the region in question. The result will be a reduction in the comparative locational advantage for the affected region and a tendency toward a relative shift in employment in national-market industries away from that region to lower-cost regions (the location effect); Third, it should be able to quantify the relative magnitudes of the factor-substitution effect and the location effect arising from any given change in regional input prices; Fourth, it should recognize that a complex set of interrelationships exists not only between the export sector and the local sector, but also among the various industries within each sector. Received for publication May 17, 1978. Revision accepted for publication December 7, 1978. * University of Massachusetts at Amherst, Massachusetts Institute of Technology, and Regional Science Research Institute, respectively. Work on this model has been supported by the Commonwealth of Massachusetts. The authors are grateful to Edward M. McNertney for contributions to the development and estimation of many of the equations and to Roy E. Williams for a mathematical and statistical review of the model and for programming the model. ' See, for example, Isard (1960), Tiebout (1962), Bourque et al. (1967), Miernyk (1970), and Polenske (1974). 2 See, for example, Weber (1928), Hoover (1937), Isard (1956) and Borts and Stein (1964). 3See, for example, Friedlaender et al. (1975), Adams et al. (1976), and Glickman (1977).